A General In Situ Growth Strategy of Designing Theranostic NaLnF4@Cu2−xS Nanoplatform for In Vivo NIR‐II Optical Imaging Beyond 1500 nm and Photothermal Therapy. Issue 6 (21st March 2019) - Jiang, Mingyang; Liu, Hongrong; Zeng, Songjun; Hao, Jianhua
Abstract: Theranostic nanoprobes with a combination of highly sensitive optical bioimaging and photothermal therapy (PTT) are considered advanced tools for improving the detection precision and the imaging‐guided hyperthermal therapy efficacy against tumor in the biomedical area. Compared with the traditional visible/first near‐infrared (NIR‐I, 650–900 nm) light‐emitting optical probe, a nanoprobe capable of generating the second near‐infrared (NIR‐II, 1000–1700 nm) emission is emerging as the next‐generation optical imaging technique with high‐sensitivity, and high spatial/time resolution owing to its remarkably reduced photon scattering losses. However, a multifunctional theranostic nanoplatform incorporated with the new advanced NIR‐II optical imaging and PTT has not yet been explored. Herein, a general strategy for designing theranostic nanoplatforms by integrating NIR‐II optical bioimaging with photothermal functions via in situ growth of Cu2− x S quantum dots on the lanthanide nanorods is demonstrated. The as‐prepared NaLnF4 :Yb/Er@Cu2− x S hybrid nanoprobes with a core‐satellite structure present excellent NIR‐II emission centered at 1525 nm, highly stable photothermal effects and good biocompatibility. These designed theranostic nanoprobes are utilized for NIR‐II optical imaging, small tumor detection (5 mm in diameter), and PTT. More importantly, non‐invasive brain vessel visualization with high spatial resolution (44.2 µm) through scalp and skull without craniotomy is demonstrated. Therefore, these results pave the way to designing new multifunction theranostic nanoplatforms for highly sensitive NIR‐II optical‐guided tumor detection, non‐invasive blood vessel imaging, and PTT. Abstract : A general in situ growth strategy for achieving an integrative NaLnF4 @Cu2− x S theranostic nanoprobe combining efficient NIR‐II emission and high‐performance PTT is demonstrated. NIR‐II imaging‐guided small tumor diagnosis and non‐invasive in vivo brain vessel imaging with high spatial resolution and PTT are achieved, providing a new opportunity for exploring highly sensitive theranostic nanoprobes by integrating NIR‐II imaging with PTT.